P84 Low rates of nucleos(t)ide-associated adverse events in the long-term experience with entecavir. (16th November 2010) - Mason, N; Manns, M; Akarca, U; Chang, T T; Sievert, W; Yoon, S K; Tsai, N; Min, A; Pangerl, A; Beebe, S; Yu, M; Wongcharatrawee, S
Abstract : Introduction: In Phase III studies evaluating treatment of chronic hepatitis B (CHB), entecavir demonstrated superior efficacy compared to lamivudine and a comparable safety and tolerability profile. Long-term safety data from the rollover study ETV-901 are reviewed, focussing on adverse events (AEs) with a potential nucleos(t)ide association. Method: Long-term cumulative safety and tolerability results are based on investigator-reported AEs, regardless of causal relationship. Results: Median exposure to entecavir in ETV-901 was 168 weeks. Of the 1045 treated patients, 402 (38%) had received entecavir for =5 years at the time of analysis. Also, 488 (47%) patients had additional prior entecavir exposure from Phase II or III participation. Baseline characteristics were: mean age 41 years; 804 (77%) male, 539 (52%) Asian, and 480 (46%) Caucasian. The most common AEs (=10%) were upper respiratory tract infection, headache and nasopharyngitis. On-treatment alanine aminotransferase (ALT) flares were reported in 3% of patients. The cumulative rate of serious AEs was 15%. Discontinuations due to AEs were 1% (n=13), and generally (n=11) occurred during the first 2 years of ETV-901. Selected AEs with a potential nucleos(t)ide association are described below. Conclusion: Entecavir is a safe and well-tolerated treatment for patients with CHB and compensated liver disease. Long-term administration of entecavir was associated with low rates of serious AEs, discontinuations due to AEs and ALT flares. Spontaneous reports of AEs potentially associated with nucleos(t)ide use occurred at low rates. Abstract P84 Table 1 Results Investigator-reported adverse events (all grades; unrelated and related to entecavir)* Median exposure 168 weeks N=1045, n (%) Elevated lipase† 21 (2) Pancreatitis 3 (<1) Blood creatinine increase 8 (<1) Hypophosphataemia† 5 (<1) Creatine phosphokinase increase† 2 (<1) Myalgia 50 (5) Muscular weakness 4 (<1) Neuropathy-related adverse events (hypo-, hyper-, paraesthesia, polyneuropathy) 39 (4) Lactate increase† or bicarbonate decrease 6 (<1) * Multiple adverse events per individual patient are possible. † No prospective testing for laboratory parameter (reactive only).